Langkah Mudah Memulai Hidroponik: dari Teori ke Praktik - Yoshida, Debbie; Alfia, Yulis Diana (Universitas Pahlawan Tuanku Tambusai, 2025)
The increasingly advanced urban growth makes cities increasingly dense. The availability of facilities and infrastructure is greatly needed by the community. Land is often converted to housing, offices, shopping centers, toll roads and other facilities. This impacts the environment, health, the economy and food production. Meruya Selatan sub-district, with its fairly dense population, has seen much land converted to housing, apartments, office buildings, malls, and toll roads that form part of the Jakarta Outer Ring Road (JORR), resulting in a lack of green spaces and limited land for planting. By using a hydroponic system, planting can be done without using soil. The purpose of this activity is to provide knowledge and skills to the women of the PKK Meruya Selatan group to easily grow vegetables through a hydroponic system and to be able to practice hydroponic vegetable cultivation. The implementation method is a training method with lectures and practical methods. The results of the activity received a positive response from participants, and hydroponic vegetables planted using the DFT system grew well until harvest.